2020
DOI: 10.3389/fagro.2020.605655
|View full text |Cite
|
Sign up to set email alerts
|

Combining Seed Dressing and Foliar Applications of Phosphorus Fertilizer Can Give Similar Crop Growth and Yield Benefits to Soil Applications Together With Greater Recovery Rates

Abstract: Phosphorus (P) fertilizers have a dramatic effect on agricultural productivity, but conventional methods of application result in only limited recovery of the applied P. Given the increasing volatility in rock phosphate prices, more efficient strategies for P fertilizer use would be of economic and environmental benefit in the drive for sustainable intensification. This study used a combination of controlled-environment experiments and radioisotopic labeling to investigate the fertilizer use efficiency of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Foliar fertilization has the potential to become a more sustainable and cost‐effective supplementary strategy to classic soil fertilization. This is already a common approach for urea‐based nitrogen fertilization, micronutrients such as manganese (Mn), and is under investigation for P (McBeath et al, 2020; Noack et al, 2010; Talboys et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foliar fertilization has the potential to become a more sustainable and cost‐effective supplementary strategy to classic soil fertilization. This is already a common approach for urea‐based nitrogen fertilization, micronutrients such as manganese (Mn), and is under investigation for P (McBeath et al, 2020; Noack et al, 2010; Talboys et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While there have been no studies investigating at the same time the effects of Mn deficiency on leaf properties and foliar nutrient absorption, it is known that Mn deficiency in barley decreased epicuticular waxes by 40% (Hebbern et al, 2009). Despite the recent increase in studies on foliar P fertilization, mixed results have been obtained and few studies have been conducted on P‐deficient plants (Froese et al, 2020; Gross et al, 2021; McBeath et al, 2020; Talboys et al, 2020). While severely P‐deficient wheat did not absorb any foliar‐applied P, foliar‐applied P was shown to successfully restored physiological function in P‐deficient barley (Arsic et al, 2020; Fernández et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the effects on biomass formation, adequate timing, as well as the optimal concentration of foliar P application were the focus of investigations. In recent years, some foliar P application studies were carried out with P deficient plant species such as wheat [ 25 , 48 , 49 , 50 , 51 , 52 ], barley [ 20 , 21 , 53 , 54 , 55 ] or maize [ 28 , 56 , 57 ]. It was shown that P deficiency can lead to alterations in the composition of plant tissues and epidermal structures such as stomata and trichomes, which ultimately affects the rate of uptake of P via foliage.…”
Section: Introductionmentioning
confidence: 99%
“…The result construed with the findings of (Adigbo et al, 2012) reported that organic liquid fertilizer is less effective and efficient than inorganic granular fertilizer. Talboys et al (2020) concluded that a double combination of seed dressing and foliar application is one of the best alternatives in offering higher efficiency in using applied nutrients relative to its uptake rate and grain productivity than single liquid organic fertilizer. In this study, the effect of foliar application of seaweed extracts was not efficiently utilized by the ratoon crop, thereby translocation of sprayed foliar fertilizers was hampered due to high temperatures of the foliage of the growing ratoon crop.…”
Section: Agronomic Characteristics and Yield And Yield Component Para...mentioning
confidence: 99%